Frequent linguistic errors in the writing of Yemeni EFL Arabic-speaking learners - Ali Mohammed Saleh Al-Hamzi; Mangatur Nababan; Riyadi Santosa; Djatmika Djatmika; Sumarlam Sumarlam; Henry Yustanto (Studies in English Language and Education, 2023)
The Yemeni EFL learners are prone to share their knowledge and views regarding what and how to say. The constraints of combining this expertise have hampered learners’ writing success. Those obstacles can cause learners to make errors. Error Analysis (EA) and Surface Strategy Taxonomy (SST) were used to analyze learners’ linguistic errors. Error causes were also investigated. This research used a qualitative process style to use a case study approach. Ellis’ five-step EA procedure was followed to analyze essay data each comprising 100-350 words or more written by 20 Yemeni EFL eighth semester Arabic-speaking learners at the Department of Education, Sana’a University, Yemen. They were purposely selected as research subjects. It was noticed that omission was the most common error detected in the learners’ writings. Overall, this form of error accounted for 58.71% of 118 cases out of 201 cases. The learners’ common error categories were the number marker, verb-tenses articles, prepositions, subject-verb agreements, and pronouns. This was preceded by addition (20.39%), incorrect formation (15.92%), and word order (4.97%). Intralingual transfer turned out to be the key reason that caused the errors in the learners’ writing. Any of the interlinguistic comparisons was the cause behind the errors. In terms of verb conjugation component, inflectional morpheme, and auxiliary verb abandonment, Arabic and English have different formal definitions. Interlingual transfer and learning context also caused errors. To prevent errors from fossilizing, language instructors should provide continual corrective feedback, and learners should pursue the correct target language form.